Literature Review Educational Management: Factors Affecting Islamic Education in The Era of Society 5.0 - Syahri, Syahri (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This article was written by the author to examine the factors that influence Islamic education. Quality education for an educational institution is currently a top priority. This is the most important part in building sustainable education, therefore educators/educational staff must have a management principle in carrying out changes or development towards quality education, especially in the era of society 5.0, not only limited to manufacturing factors but also solving social problems with the help of the integration of physical and virtual space. In facing the era of society 5.0, the world of education plays an important role in improving the quality of human resources. Apart from education, several elements and stakeholders such as the government, Community Organizations (Ormas) and the entire community also take part in welcoming the upcoming era of society 5.0. Furthermore, writing this article uses qualitative writing methods and literature study or Library Research. The results of this study show that we know the factors that influence Islamic education in the era of society 5.0 Education that requires a process of instilling in a way of life that is mutually respectful, sincere and tolerant towards the cultural diversity that lives in the era of society 5.0. Interrelationships In carrying out Islamic education management, these factors are important to pay attention to and manage. educators, curriculum and work culture which can influence the process and quality of educational institutions.